2004
DOI: 10.1366/000370204774103408
|View full text |Cite
|
Sign up to set email alerts
|

Part I: Surface-Enhanced Raman Spectroscopy Investigation of Amino Acids and Their Homodipeptides Adsorbed on Colloidal Silver

Abstract: Surface-enhanced Raman scattering spectra (SERS) were measured for various amino acids: L-methionine (Met), L-cysteine (Cys), Lglycine (Gly), L-leucine (Leu), L-phenylalanine (Phe), and L-proline (Pro) and their homodipeptides (Met-Met, Cys-Cys, Gly-Gly, LeuLeu, Phe-Phe, and Pro-Pro) in silver colloidal solutions. The geometry and orientation of the amino acids or dipeptides on the silver surface, and their specific interaction with the surface, were deducted by detailed spectral analysis of the SERS spectra. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
239
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(258 citation statements)
references
References 85 publications
17
239
0
1
Order By: Relevance
“…Similar observations have been reported in the literature. For example, Hu et al 56 reported the appearance of an amide 2 band ͑centered at 1526 cm −1 ͒ in the SERS spectrum of lysozyme, Kim et al 57 observed the presence of this band ͑at 1520 cm −1 ͒ in the SERS spectrum of Gly-L-Phe dipeptide, and Podstawka et al 58,59 observed this band from 1504 to 1554 cm −1 in the SERS spectra of a series of homoand heterodipeptides.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been reported in the literature. For example, Hu et al 56 reported the appearance of an amide 2 band ͑centered at 1526 cm −1 ͒ in the SERS spectrum of lysozyme, Kim et al 57 observed the presence of this band ͑at 1520 cm −1 ͒ in the SERS spectrum of Gly-L-Phe dipeptide, and Podstawka et al 58,59 observed this band from 1504 to 1554 cm −1 in the SERS spectra of a series of homoand heterodipeptides.…”
Section: Resultsmentioning
confidence: 99%
“…A solution of the colloidal silver was prepared three times according to the standard procedure. 27 Briefly, 8.5 mg of AgNO 3 dissolved in 50 ml deionized water at 4°C was added dropwise to 150 ml of 1 mM solution of NaBH 4 immersed in an icebath and stirred vigorously. After the addition of AgNO 3 was completed, the resulting pale-yellow solution was stirred and maintained at 4°C for approximately 1 h. The excitation spectra of three batches of the Ag sol prepared in this manner showed an absorbance maximum at 396 nm.…”
Section: Sers Spectroscopymentioning
confidence: 99%
“…This may help in understanding their biological activity in the physiological conditions at the basic pH. The information obtained is also useful in understanding the adsorption process of amino acids, 27,28 peptides, 28 -31 or proteins 32,33 at the aqueous solution/silver (gold) interface.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed examination of the SERS behaviour of amino acids, homodipeptides, and heterodipeptides was covered by Podstawka, Ozaki, and Proniewicz [21,22]. In these studies, there is extensive discussion on vibrational assignments of bands in the Raman spectra.…”
Section: Sers Of Small Biological Moleculesmentioning
confidence: 99%